Composición de una rapsodia musical incorporando elementos de los géneros ecuatorianos: danzante, yaraví, sanjuanito - Vélez Sócola., Tabita Nayely (2023)
Artistic expressions are important in the life of the human being, as they are part of a social group directly related to culture. Music facilitates communication between individuals, beyond words, making it possible to share feelings and meanings, promoting cultural development and a sense of belonging among communities. Over time, as a result of globalization, musical preferences have become alienated and, as a result of this process, preference is given to foreign rhythms, causing the disregard of traditional musical rhythms that are part of the cultural identity of a given place. Therefore, the objective of this research contributed to the local compositional development through the creation of a musical rhapsody incorporating elements of Ecuadorian genres such as the yaraví, the danzante and the sanjuanito. Within the present Curricular Integration Work, it was channeled from a qualitative methodological approach whose non-experimental design was supported by artistic research, the results were based on the sound discrimination of Ecuadorian musical genres, whose inputs allowed the conception of the artistic product. The musical composition in rhapsody format, incorporates the traditional elements of the musical genres mentioned above, integrated in a free way taking into account: the melodic bases such as the use of pentaphony, mishky note, harmonics and rhythmic variations typical of Ecuadorian music. From this material it is estimated to strengthen the compositional field and the cultural identity through interpretation. It is thus defined as a conclusive part of this study, in which it is mentioned that Ecuadorian music has interesting elements that allow in a free and dynamic way to carry out a compositional process, whose range of musical possibilities allow future generations to bet on this type of composition. Keywords: composition, rhapsody, cultural identity, ecuadorian music